Massive unilateral hemothorax: a rare complication of severe dengue in the outbreak in Peru - Rojas Díaz, Marcelo (2025)
Introduction: Dengue is an acute febrile disease caused by the dengue virus, transmitted by the bite of Aedes mosquitoes. It causes disease ranging from asymptomatic forms to severe illness leading to death. Piura, a department in the north of Peru, has had a dengue epidemic in 2023. Case report: a rare complication is described in a 41-year-old woman with severe dengue fever presenting with chest pain, exertional dyspnea, absence of vesicular murmur in the hemithorax, and imaging studies showing massive right pleural effusion.   Conclusion: This is a rare and previously undescribed complication in a dengue outbreak in Peru. It is necessary to recognize massive hemothorax as a complication of severe dengue, especially in endemic areas.